Formulation and Evaluation of Extended Release Carbamazepine Matrix Tablets - MANIVANNAN, R.; BALASUBRAMANIAM, A.; SANDEEP, G.; IBRAHIM AFSAL, V.T. (Asian Journal of Chemistry, 2010)
The aim of study was to prepare and characterize extended release matrix tablets of carbamazepine using hydrophilic polymers like HPMCK-100M, AVICEL PH-102 with or without HPMC K4M. Release kinetics evaluated by using USP-22 TYPE-I dissolution apparatus. The newly formulated extended release tablets of carbamazepine were compared with conventional marketed tablet. The in vitro drug release study revealed that HPMC K-100M formulation was able to sustain the drug release for 15 h (90.93 %). Fitting the in vitro drug release data to Koresmeyer equation indicated that diffusion along with erosion could be the mechanism of drug release. Further evaluation by DSC thermogram and FTIR studies conclude that no interaction between polymer and drug. The results suggest that the developed extended release tablets of carbamazepine could perform therapeutically equivalent to conventional dosage forms, leading to better patient compliance.